Increased Autolysis of μ‐Calpain in Skeletal Muscles of Chronic Alcohol‐Fed Rats. (21st September 2017) - Gritsyna, Yulia V.; Salmov, Nikolay N.; Bobylev, Alexander G.; Ulanova, Anna D.; Kukushkin, Nikolay I.; Podlubnaya, Zoya A.; Vikhlyantsev, Ivan M.
Abstract : Background: Proteolysis can proceed via several distinct pathways such as the lysosomal, calcium‐dependent, and ubiquitin–proteasome‐dependent pathways. Calpains are the main proteases that cleave a large variety of proteins, including the giant sarcomeric proteins, titin and nebulin. Chronic ethanol feeding for 6 weeks did not affect the activities of μ ‐calpain and m‐calpain in the m. gastrocnemius. In our research, changes in μ ‐calpain activity were studied in the m. gastrocnemius and m. soleus of chronically alcohol‐fed rats after 6 months of alcohol intake. Methods: SDS‐PAGE analysis was applied to detect changes in titin and nebulin contents. Titin phosphorylation analysis was performed using the fluorescent dye Pro‐Q Diamond. Western blotting was used to determine μ ‐calpain autolysis as well as μ ‐calpain and calpastatin contents. The titin and nebulin mRNA levels were assessed by real‐time PCR. Results: The amounts of the autolysed isoform (78 kDa) of full‐length μ ‐calpain (80 kDa) increased in the m. gastrocnemius and m. soleus of alcohol‐fed rats. The calpastatin content increased in m. gastrocnemius. Decreased intact titin‐1 (T1) and increased T2‐proteolytic fragment contents were found in the m. gastrocnemius and m. soleus of the alcohol‐fed rats. The nebulin content decreased in the rat gastrocnemius muscle of the alcohol‐fed group. The phosphorylation levels of T1 and T2 were increased in the m. gastrocnemius and m. soleus, and decreased titin and nebulin mRNA levels were observed in the m. gastrocnemius. The nebulin mRNA level was increased in the soleus muscle of the alcohol‐fed rats. Conclusions: In summary, our data suggest that prolonged chronic alcohol consumption for 6 months resulted in increased autolysis of μ ‐calpain in rat skeletal muscles. These changes were accompanied by reduced titin and nebulin contents, titin hyperphosphorylation, and development of hindlimb muscle atrophy in the alcohol‐fed rats.